Transformada Inversa de Laplace - Oviedo-Ugalde, Norberto Gerardo (My University, 2019)
En la presentación se explica en un primer momento definición y propiedades de linealidad de la transformada inversa de Laplace. Posteriormente mediante dos ejemplos se ilustra dicha definición y uso de propiedades de linealidad de la transformada inversa de Laplace, en la cual además se recurre al uso de trasformadas por medio de tabla de transformadas.

In the presentation, definition and linearity properties of the Laplace inverse transform are explained at first. Subsequently, by means of two examples, this definition and use of linearity properties of the Laplace inverse transform is illustrated, in which the use of transformations is also used by means of a table of transformations.
Keywords: Transformada inversa de Laplace; Ecuaciones diferenciales; Matemáticas; Tablas; Inverse Laplace transform; Differential equations; Mathematics; Boards